133k views
2 votes
Show that a = −1 + √3i and b = 2 satisfy 1/a+b=1/a + 1/b

1 Answer

0 votes

Answer:

LHS =
(1 - \sqrt3i)/(4) = RHS =
(1 - \sqrt3i)/(4)

Explanation:

Data provided in the question:

a = −1 + √3i and b = 2

to prove:


(1)/(a+b)=(1)/(a) + (1)/(b)

Considering the LHS


(1)/(a+b)

substituting the value of a and b, we get


(1)/(−1 + \sqrt3i+2)

or


(1)/(1 + \sqrt3i)

on multiplying and dividing by conjugate ( 1 - √3i )

we get


(1)/(1 + \sqrt3i)*(1 - \sqrt3i)/(1 - \sqrt3i)

or


(1 - \sqrt3i)/((1^2 - (\sqrt3i)^2)

or


(1 - \sqrt3i)/(1 + 3) (as (√i)² = -1 )

or


(1 - \sqrt3i)/(4)

Now,

considering the RHS


(1)/(a) + (1)/(b)

substituting the value of a and b, we get


(1)/(-1 + \sqrt3i) + (1)/(2)

or


(2*1 + ( -1 + \sqrt3i)*1)/((-1 + \sqrt3i)*2)

or


(2 + ( -1 + \sqrt3i))/((-1 + \sqrt3i)*2)

or


(1 + \sqrt3i)/((-1 + \sqrt3i)*2)

now,

on multiplying and dividing by conjugate ( -1 - √3i )

we get


(1 + \sqrt3i)/((−1 + \sqrt3i)*2)*(-1 - \sqrt3i)/(-1 - \sqrt3i)

or


(1 + \sqrt3i)/((−1 + \sqrt3i)*2)*(-1( 1 + \sqrt3i))/(-1 - \sqrt3i)

or


\frac{(1 + \sqrt3i}^2*(-1){((-1)^2 - (\sqrt3i)^2)*2}

or


((1^2 + (\sqrt3i)^2+2(1)(\sqrt3i)*(-1))/((1 + 3)*2)

or


((1 - 3 + 2\sqrt3i)*(-1))/((4)*2)

or


((-2 + 2\sqrt3i)*(-1))/((4)*2)

or


(-2( 1 - 2\sqrt3i)*(-1))/((4)*2)

or


(( 1 - 2\sqrt3i))/((4))

Since, LHS = RHS

hence satisfied